The Negative Stereotypes in SAIA Short Story Anthology by Djenar Maesa Ayu - Silvi Nopianti; Tanti Agustiani; Hera Wahdah Humaira (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
Djenar Maesa Ayu's anthology of short stories SAIA tells about female characters who experience injustice caused by negative stereotypes against women in society. Here, the researcher chose three short stories entitled “Mata Naked”, “Fantasi Dunia”, and “Girl Matches”. The research method used is qualitative with analytical descriptive method and uses a feminist literary criticism approach. This study reveals the negative stereotypes contained in the three short stories which include gender prejudice and gender injustice. Keywords: short story, negative stereotype, feminist Abstrak Antologi cerpen SAIA Karya Djenar Maesa Ayu menceritakan tentang tokoh perempuan yang mengalami ketidakadilan diakibatkan oleh stereotip negatif terhadap perempuan dikalangan masyarakat. Di sini peneliti memilih tiga cerpen yang berjudul “Mata Telanjang”, “Fantasi Dunia”, dan “Gadis Korek Api”. Metode penelitian yang digunakan adalah kualitatif dengan metode deskriptif analitik dan menggunakan pendekatan kritik sastra feminis. Penelitian ini mengutarakan stereotip negatif yang terdapat dalam ketiga cerpen tersebut yang meliputi prasangka gender dan ketidakadilan gender. Kata kunci: cerpen, stereotip negatif, feminis